HEALTH VOCABULARY IN ENGLISH: INTRODUCING HOW TO APPLY HAND WASHING IN ENGLISH FOR EARLY CHILDHOOD EDUCATION IN TPA RADHATUL MAKMUR PRINGSEWU - Fini Widya Fransiska; Esa Pratama Putra (Education Studies and Teaching Journal (EDUTECH), 2025)
Early vocabulary acquisition is an important foundation for children's future literacy development and academic achievement. Simultaneously, introducing healthy lifestyle practices, such as handwashing, plays a crucial role in shaping preventive behaviors from an early age. This study examines the effectiveness of teaching health-themed English vocabulary through handwashing activities to early childhood children at Radhatul Makmur Kindergarten in Pringsewu, Indonesia. Using a narrative review approach and thematic synthesis methods, the study analyzed recent literature from leading academic databases, including Scopus, ERIC, and ScienceDirect. The results indicate that physical activity-based approaches, specifically Total Physical Response (TPR) and Content and Language Integrated Learning (CLIL), significantly strengthen vocabulary acquisition and retention and foster children's multisensory engagement. The integration of daily hygiene activities into language learning not only supports linguistic development but also contributes to character building and health awareness in children. These findings highlight the importance of contextual, experiential, interdisciplinary teaching strategies in early childhood education. The study recommends the development of a bilingual thematic curriculum that utilizes daily routines as a natural and meaningful means of language acquisition.